CONSUMPTION OF EDIBLE-INSECTS: THE CHALLENGES AND THE PROSPECTS - Nura Abdullahi; Enerst Chukwusoro Igwe; Munir Abba Dandago; Alkasim Kabiru Yunusa (Food ScienTech Journal, 2021)
Alternative sources of proteins are necessary to tackle the foreseeing challenge of protein scarcity. Insects were among the foods consumed by early man and they are still vital components in the diets of Asia, Africa, and Latin America. Social barriers are limiting their global acceptance, their consumption is intimately attached to location and culture, and their nutritional values are not known to many. Their consumption is associated with taboos and pessimisms, and are seen as something filthy, not something decent to be consumed. Literature used was gathered through an online search on Google Scholar and Science Direct database. Disgust, food neophobia, lack of awareness, unavailability, and personality traits are the major barriers to edible-insect acceptance among consumers. Accepting edible-insects as food depends greatly on location, eating habit, prior experience, age, gender, and religion of a consumer. Follow-up studies after the first introduction will give clues on the acceptance level, help understand reasons for the rejection, and allows the application of alternative and better solutions to rejection problems. Entomophagy advocate should intensify their efforts and attract more consumers in the West and other parts of the globe. Research collaborations between applied and social sciences are necessary to win the affection of new consumers and convinced their psych and emotion during the first introduction. Creating awareness on the nutritional, health, and environmental benefits of using insects as a novel protein, processing to completely mask insect presence, and producing products with a close resemblance with meat will certainly promote global insect consumption.